33 The impact of social media on anxiety and depression among patients with neuroendocrine carcinoma of the cervix: a Neuroendocrine Cervical Tumor Registry (NeCTuR) study - Reem Saab; Gloria Salvo; Naomi R. Gonzales; Mark Munsell; Eileen Shinn; Michael Frumovitz (Elsevier, 2023)
Objectives: Neuroendocrine carcinoma of the cervix (NECC) accounts for less than 1-2% of all cervical cancers. The rare nature of this disease is reflected in the limited educational resources available to patients, often leading them to seek information online through patient-led social networks. The objectives of this study were to: (1) examine social media use among NECC patients; and (2) examine their levels of anxiety and depression, and (3) correlate anxiety and depression levels with social media use. Methods: Seven surveys that assess social media use, anxiety, depression, and quality of life were distributed to known to be alive NECC patients enrolled in our Neuroendocrine Cervical Tumor Registry (NeCTuR). The primary outcome was the association between the Social Network Time Use Scale (SONTUS) global score and both the Generalized Anxiety Disorder (GAD-7) and the Center for Epidemiologic Studies Depression Scale (CES-D) total scores. Spearman's rank correlation and logistic regression were used for statistical analysis. Results: Eighty-eight patients enrolled in the study. Eighty-one patients who fully or partially completed the surveys were included.Most patients (97%) are low to average social media users. Regarding the Sisters United Facebook page, a NECC patient-led support group, 53 patients (74%) visited the page in the past 2 weeks and out of those, 42 patients (79%) reported receiving useful information. Among those who didn't visit the page (n=19), 9 patients (47%) reported that the online support group elicited anxiety and/or sadness. The mean GAD-7 and CES-D scores for the entire cohort were 7.3 and 18.1, respectively. The Spearman correlations between social media use and both anxiety and depression levels were significant (0.23 (p=0.05), GAD-7 and 0.25 (p=0.04), CES-D). The estimated odds ratio for moderate/severe anxiety as a function of the SONTUS global score was 1.26 (95% CI 1.03 to 1.55) (p=0.03) and that of depression was 1.23 (95% CI 1.01 to 1.49) (p=0.04). Conclusions: NECC patients demonstrated average social media use and relatively high levels of anxiety and depression. There seems to be an association between increased social media use and both anxiety and depression.